2015
DOI: 10.1002/ardp.201400283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Bis‐1,3,4,2‐triazaphospholinoalkane Derivatives as In Vitro α‐Amylase and Lipase Inhibitors

Abstract: A series of new 1,ω-bis-(5-alkyl-2-oxide-3-tosyl-1,3,4,2-triazaphospholino)alkanes 2 and 3 were prepared in good yields by the treatment of 1,ω-bis-(1-tosylamidrazone)alkanes 1 with two molar equivalents of phosphoryl trichloride and phenylphosphonic dichloride, respectively. All the newly synthesized compounds were characterized by IR, (1) H NMR, (13) C NMR, (31) P NMR, and elemental analysis. All the new compounds were screened for their inhibitory effect on the key enzymes related to diabetes and obesity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Inhibitors of digestive enzymes have been used for a long time as medicines in the treatment of severe forms of obesity to create artificial malabsorption of nutrients. This approach to the treatment of obesity continues to develop actively [13][14][15][16][17]. Disclosure of the detailed mechanism of the development of obesity, associated with energy metabolism disorders at this stage, requires the description of the role of various hormones, not only those produced by the "classical" endocrine glands, but also by cells of the gastrointestinal tract, liver, adipose tissue, various parts of the brain, muscles and other tissues.…”
Section: The Stage Of Digestion and Assimilation Of Nutrient Digestiomentioning
confidence: 99%
“…Inhibitors of digestive enzymes have been used for a long time as medicines in the treatment of severe forms of obesity to create artificial malabsorption of nutrients. This approach to the treatment of obesity continues to develop actively [13][14][15][16][17]. Disclosure of the detailed mechanism of the development of obesity, associated with energy metabolism disorders at this stage, requires the description of the role of various hormones, not only those produced by the "classical" endocrine glands, but also by cells of the gastrointestinal tract, liver, adipose tissue, various parts of the brain, muscles and other tissues.…”
Section: The Stage Of Digestion and Assimilation Of Nutrient Digestiomentioning
confidence: 99%
“…Past research has demonstrated the importance of five‐membered nitrogen heterocycles on PL inhibitory profiles. For instance, oxadiazole (Point et al., 2012), 1,2,4‐triazole (Bekircan et al., 2014; Kahveci et al., 2017), triaza‐phospholinoalkanes (Hamzaoui et al., 2015), rhodanine (Chauhan et al., 2019), thiazolidinedione (Sridhar, Bhurta, et al., 2017) etc. have explored for PL inhibition.…”
Section: Introductionmentioning
confidence: 99%